THE IMPLEMENTATION OF EXTENSIVE READING PROGRAM USING XREADING: STUDENTS’ PERCEPTIONS (RETAIN, 2020)
Extensive reading (ER) has been proven to have positive effects in improving students’ skills at learning English. It is believed as the strategy that can encourage students to develop their English skills such as vocabulary size, reading comprehension and fluency, as well as their grammar. As the foreign language department, English department of Universitas Negeri Surabaya always conducted the activity for the students intended to encourage them to develop their language skills. Extensive reading has been one of the activities that have been carried out to support the students in developing their English skills. By the odd semester of 2019, extensive reading program at English department had shifted from paper-based extensive reading to online-based extensive reading program using XReading platform. It is a qualitative study since it aims to investigate how the students conduct the online-based extensive reading as well as examine their perceptions of the platform as well as its effectiveness in helping the students to improve their English skills. 68 students of English Education students were participated in the study. The data was taken using questionnaire and interview. The questionnaire was distributed to the students followed by the interview aimed at the students who did not give clear explanation in the questionnaire. The result of the study showed that the implementation of extensive reading program were mostly done at home with utilizing some features offered by the platform and positive responses about the XReading platform also given by the students as well as their improvement in some aspects of English ability. Suggestion are made on the further activity in the classroom that would be better to be carried out as the continued activity of what was done by the students at home as well as the routine surveillance by the supervisor should be tightened up.